Principles of Development of Engineering Ecology (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Nowadays, the population of the earth has increased several times from the beginning of the last century to the present day of the new century. This in turn led to the construction of many factories, construction of roads, construction of houses, increase of motor vehicles and many similar activities in the countries in order to provide them with vital products. . As a result, nature has been used and is being used mercilessly, and it itself is overflowing with various wastes. If the situation continues at this level, the existence of humanity on earth will be in danger in the near future. Therefore, regardless of the class of the industrial network, every enterprise should pay serious attention to the complete decontamination and cleaning of the wastes released from it.